Equity risk premium in ASEAN: Analysis on its puzzle, behavior and effect of selected macroeconomic variables - Moron, Katherine Villalobos (Animo Repository, 2016)
This paper aims to mainly investigate equity risk premiums of the six major members of ASEAN countries such as Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam which are selected based on their stock market development and data availability. It has focused on the three different issues of the equity risk premium such as the intriguing issue on the existence of equity premium puzzle, its behavior and impact of selected macroeconomic variables on equity risk premium. For the first part of the paper which is to determine whether the puzzle exists, it has employed three methods to test this phenomenon, (1) basic model consumption of Mehra and Prescott (1985) and simplified model by Ni( 2006); (2) calibration (Campbell, 2003) and (3) GMM estimation (Hansen, 1982). The calibration method results suggest that the puzzle exists in Indonesia.2008 Financial crisis cannot explain the occurrence of the puzzle but shows to have potential impact on the trend of equity risk premium. Also, sub-sample analyses through GMM indicate that ASEAN investors tend to be more decreasing averse and prefer to have utility tomorrow than today after the crisis. Selected macroeconomic variables such as Gross Domestic Product (GDP), inflation (INF), foreign direct investment (FDI) and stocks traded turnover ratio (STTR) are regressed on equity risk premium (ERP). Applied methods are panel pooled regression and panel vector error correction model (VECM) through the latest version of Eviews9. In the former approach, only INF significantly and negatively affects the ERP. Both periods and years show to have fixed effects as dummy variables. Panel VECM and Granger Casuality test infer both long and short-run relationship exists in the system.